The Effect of Capital Expenditure, Balancing Funds, and Special Financial Assistance (BKK) on The Welfare of the People of Central Java Post Covid-19 (2020-2022) - Pangestuti, Ana Fauziah; Wibowo, Hardiyanto; Fakhruddin, Iwan; Santoso, Selamet Eko Budi (East Asian Journal of Multidisciplinary Research, 2024)
This study examines the impact of capital expenditure, balancing funds, and special financial assistance (BKK) on community welfare in 35 districts/cities of Central Java Province from 2020-2022 with a total of 105 data, with multiple linear regression analysis techniques and assisted by the STATAMP 17 calculation tool. The study employs a quantitative model using secondary data and multiple linear regression analysis approaches using the HDI measurement indicator. The findings indicate that although BKK has no beneficial impact on human wellbeing, capital spending and balancing money do. The study aims to provide a deeper understanding of these factors' influence on community welfare, helping policymakers develop more effective and sustainable budget strategies to improve community welfare through efficient allocation of funds.